Surgical Site Infections are the Pool of Antibiotic Resistant Bacteria: Evidence from a Tertiary Hospital in Nepal - Adhikari, Sanjib; Khadka, Sujan; Sapkota, Sanjeep; Adhikaree, Neetu; Shrestha, Barsha; Parajuli, Ashish (Anti-Infective Agents, 2021)
Background: Surgical site infections (SSIs) are the leading nosocomial infections and important cause of morbidity and mortality in surgical patients. Objective: The present study was conducted to investigate the bacterial etiology of SSIs and determine the antibiotic susceptibility patterns of the isolates. Methodology: A cross-sectional study was conducted between July to November 2019 on 105 patients suspected of having SSIs. Wound swabs were collected aseptically using sterile cotton swabs and processed in suitable culture media following the standard operative protocols. Antibiotic susceptibility testing was done by Kirby-Bauer disc diffusion technique following Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Out of 105 samples collected, 69 showed growth and 77 bacterial isolates were documented altogether. The most frequently isolated bacteria were Staphylococcus aureus 46 (59.74%) followed by E. coli 9 (11.68%). The antimicrobial profile of the isolates revealed that 61.04% were MDR, 25.80% were ESBL producers and 9.68% were carbapenemase producers. Conclusion: High prevalence of antibiotic-resistant bacterial isolates associated with SSIs warrants the need for aseptic techniques during and after surgical procedures and judicious use of antibiotics.
Keywords: MDR